A simple novel technique [PUIT] for closure of urethrocutaneous fistula after hypospadias repair: Preliminary results - M S Awad (Indian Journal of Plastic Surgery)
Urethrocutaneous fistula is a common complication of urethroplasty for severe hypospadias, even when a microsurgical technique is applied, the closure of the fistula is a challenging problem. We present a simple surgical procedure, posterior urethral incision technique [PUIT] to close the fistula in our department. Between February 2001 and December 2004 we prospectively evaluated 32 patients, 26 patients with initial hypospadias fistulas and 6 with recurrent fistulas who underwent closure of urethrocutaneous fistula after hypospadias repair. The mean age of patients was 5 years, the operation consisted of trimming the fistula edge after mobilization of the skin all-around then a midline posterior urethral incision was done 2 mm above and 2 mm below the fistula opening then re-approximation of the urethral edges using 6/0 vicryl sutures with loop magnification. The timing of fistula repair was between 6 and 13 months after it was formed, all of these were effectively closed except three cases with stricture and fistula. Of these, two were completely relieved after repeated urethral dilatation, three times a week for 2 weeks. The third failed case will need another sitting after 6 months. The posterior midline urethral incision gives a good opportunity for repair without tension with a good cosmetic outcome. This may be done under local anesthesia in adults. The procedure is considered simple rapid and easy to be done for variable fistulas types whatever of its site and the age.